Sediment Accretion and Variabllity of Sedimentological Characteristics of a Tropical Estuarine Mangrove: Kemaman, Terengganu - Saad, Shahbudin (1996)
The study on the sediment accretion and variability of sedimentological characteristics were conducted on an estuarine mangrove in the Kemaman district with the aims of determining the average annual accretion rate, the monthly accretion rate variability, sediment distribution and its variability within the mangrove area. The study was conducted over a two year period starting from September 1993 to August 1995. The average accretion rate for the first and second year of study were found to be 0.66 cm/yr and 1.46 cm/yr respectively, while the average for the entire study period was 1.06 cm/yr. Accretion rate rate was found to be higher at the front mangrove and gradually becoming smaller towards the back mangrove. This trend was found to be true for both the monsoon and the non-monsoon seasons. Nevertheless, the accretion rate on the entire mangrove area was higher during the monsoon months compared to the non-monsoon months. Sedimentologically. the surface sediment of the Kemaman mangrove consists of sediment ranging from very fine sand to medium silt. The surface sediment tended to become finer, better sorted and more positively skewed towards the back mangrove. The average of mean size of surface sediment was found to be 4. 17 phi (coarse silt). The average of standard deviation, skewness and kurtosis of the surface sediment were 1.99 phi (poorly sorted), 0.05 (symmetrical) and 2.33 phi (very leptokurtic), respectively. While the parameters of mean size and skewness do not differ between the monsoon and the non-monsoon seasons, the parameters of standard deviation and kurtosis tended to become better sorted and more peaked respectively during the monsoon season. The higher accretion rates indicate that the Kemaman mangrove is still in the process of finding an equilibrium level with the major environmental forces affecting it. It is also interesting to note that the accretion rates during the monsoon season are significantly high compared to the non-monsoon season indicating the role of the monsoon in supplying sediments to the mangrove area.